The Effectiveness of Online Learning Using Google Workspace and WhatsApp Applications - Sudrajat, Jajat; Permana, Ibar Adi; Azizah, Nur (Society, 2022)
This study aims to find an effective online learning strategy during the COVID-19 pandemic in teaching Mathematics subject matter to Class X MIPA of State Senior High School 1 Lubuklinggau. The strategy in this classroom action research is carried out through 2 cycles and includes planning, implementing, observing and reflecting. At the same time, questionnaires online were distributed to the student to find out the initial state of the study. The object of this classroom action research was class X MIPA of State Senior High School 1 Lubuklinggau. The results of classroom action research with two cycles show an increase in the results achieved according to the indicators of success. In the first cycle of students who took part in learning, as much as 79% experienced an increase of 6% in cycle II of 85% of students who took part in learning. In terms of timeliness of students in collecting assignments also increased by 5% from the first cycle of 72% to 77%. This proves that more than 75% of students participate in online learning and collect assignments on time.